Hubungan Self Management Dengan Tingkat Kecemasan Pasien Diabetes Melitus Yang Menjalani Diet di Wilayah Kerja Puskesmas Jampang Tengah Kabupaten Sukabumi - Muhamad Asep Zaenudin; Irawan Danismaya; Sri Kurnia Dewi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Diabetes Mellitus is a condition that continues to worsen and requires adjustments to one's way of life, especially regarding diet. This adjustment can cause anxiety for the individual who experiences it, so self-management is needed in the diabetes treatment process. Objective: To determine the relationship between self-management and the anxiety level of diabetes mellitus patients who are on a diet at the Jampangtengah Community Health Center, Sukabumi. Method: Cross-sectional research with 79 samples using purposive sampling. Data analysis was carried out using the chi-square test. Results: The statistical test shows a p value = 0.000 (<0.05), which means there is a significant relationship between self-management and the anxiety level of diabetes mellitus patients who are on a diet in the working area of ??the Central Jampang Health Center, Sukabumi Regency. Conclusion: There is a relationship between self-management and the anxiety level of diabetes mellitus patients who are on a diet.